International trade and the adaptation to climate change and variability - Gunter Stephan; Oliver Schenker (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
This paper has three messages mainly, which are observed in a simple model of climate change, international trade and regional adaptation. First, trade can be viewed as a kind of adaptation to climate change and variability, as trade can help to reduce direct impacts of global climate change on a region's welfare. In particular, the less affected and the richer nations are, the more they can profit from moderating the impacts of global climate change through trade. Second, if regions are rich enough to adapt optimally to climate change, the resulting allocation of adaptation measures is Pareto-efficient. In this case funding of adaptation, which is an element of international climate policy, does not make sense from an economic perspective. Third, since the regions of the South typically lack the resources for adapting optimally to climate change, because of terms of trade effects, it might be in the selfinterest of the industrialized nations to fund adaptation in the developing part of the world. However, providing financial assistance for adaptation can be Pareto-improving only, if the benefits of funding, i.e., damages, which are moderated through adaptation, are big enough, and hence, if the recipient's own expenditure for adaptation is low. If not, the paradoxical effect of recipient immiserization through tied transfers can occur.
Keywords: F18; Q56; Q54; 330; Funding of adaptation; climate change; international trade